Pride, Faith, and Fear: Islam in Sub-Saharan Africa by Charlotte A. Quinn and Frederick Quinn (USA: Oxford University Press, 2003. 175 pages.) (American Journal of Islam and Society, 2004)
If the real value of a book – any book – comes from its ability to presentitself as a subject of various, but not contradictory, readings, this bookundoubtedly fulfils that value. From the point of view of a Muslim and nonwesternreader, the book reflects the western fear of Islam as a power in crisisbut adopts a line of argument against mainstream western writings on Islam. In other words, it argues against the prevalent claim that Islam, especiallyafter the collapse of communism, represents the most dangerous threatto western values. Further, the book suggests that “opportunities for positiveengagement with Africa’s Muslim communities and states abound on thepolitical, social, religious, economic, and cultural level” (p. 150).Motivated by the need “to find a reasonable avenue of exploration andaccommodation with countries and cultures that differ from our own (theWestern culture),” the book unveils the mutual misunderstanding betweenthe West and the Muslim world. Thus, it argues that the “Muslim world istreated (by the West) as having a single dimension, as if Muslims in generalhad bonded with Osama bin Laden” (p. 4). It also argues that the Westsees Muslims as “stubbornly holding the idea that Christians have not abandonedthe Crusaders’ mentality, zealously trying to destroy all traces ofMuslim civilizations in their entirety” (p. 4). Being aware of the harmfulimpacts of these misleading images not only on the media, but also – andthis is the most dangerous – on the “contemporary (academic) analysis,”the book invites the People of the Book (ahl al-kitab) to work togethertoward peace and reconciliation, emphasizing that “it will be a difficult butnot impossible road.” Without this effort to make peace, the book suggests,there will be chaos and violence ...